2019
DOI: 10.3389/fendo.2019.00433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin on the Defense to Acute Hypoxia in Newborn Lambs

Abstract: Neonatal lambs, as other neonates, have physiologically a very low plasma melatonin concentration throughout 24 h. Previously, we found that melatonin given to neonates daily for 5 days decreased heart weight and changed plasma cortisol and gene expression in the adrenal and heart. Whether these changes could compromise the responses to life challenges is unknown. Therefore, firstly, we studied acute effects of melatonin on the defense mechanisms to acute hypoxia in the neonate. Eleven lambs, 2 weeks old, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…MT is synthesized by the pineal gland, in the bone marrow, the eyes and the gastrointestinal tract. The synthesis of MT arises from 5-hydroxytryptamine and the rate-limiting enzyme in this reaction is MT-N-acetyltransferase (9). Certain researchers have indicated that MT can lighten mottled skin by downregulating melanophores (10,11) Moreover, MT regulates the human chronobiological function known as the circadian rhythm (12).…”
Section: Introductionmentioning
confidence: 99%
“…MT is synthesized by the pineal gland, in the bone marrow, the eyes and the gastrointestinal tract. The synthesis of MT arises from 5-hydroxytryptamine and the rate-limiting enzyme in this reaction is MT-N-acetyltransferase (9). Certain researchers have indicated that MT can lighten mottled skin by downregulating melanophores (10,11) Moreover, MT regulates the human chronobiological function known as the circadian rhythm (12).…”
Section: Introductionmentioning
confidence: 99%
“…The most interesting mechanism by which melatonin can improve physiological cardiovascular oscillations is probably its epigenetic action on the adrenal glands and the heart. Melatonin modifies the genetic expression of NR3C1, the glucocorticoid receptor, in the adrenal gland and the heart [53]. In particular, melatonin reduces the NR3C1 gene in the heart and increases it in the kidneys and lungs.…”
Section: Melatonin's Epigenetic Actionsmentioning
confidence: 99%
“…Treatments for pulmonary hypertension have been in the spotlight for the last 20 years, mainly aimed at reducing the intense vasoconstriction, the risks of blood-clots and on increasing pulmonary vasodilatation ( Navarrete et al, 2020 ). Several studies focused on vascular reactivity have assessed the influence of a melatonin treatment and its effect on chronic HAHH ( Beñaldo et al, 2019 ; Figueroa et al, 2021 ; Gonzaléz-Candia et al, 2021 ). From a biomechanical point of view, the performance of different treatments applied in the aforementioned context on the passive mechanical response of arteries, has not been widely assessed.…”
Section: Introductionmentioning
confidence: 99%